INTERNALIZATION OF RELIGIOUS VALUES BASED PESANTREN (Study of SMA Muhammadiyah 01 Metro Lampung): Analysis of the study in Muhammadiyah High School 01 Metro Lampung - Maragustam, Maragustam; Wibisono, Yogi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
Action or morality in principle begins with a deep value in the soul. That deep value becomes a pattern of belief, awareness, and thought. Because that value has become a mindset, taste, and belief, one will easily do positive and negative actions. So, the planting of value becomes a necessity in education. This research will answer how the school's strategy instills religious values, what religious values are instilled, its supporters and inhibitions, and how they result. This type of research is qualitative with a pedagogical approach. Determination of subjects using purposive and Snowball. Data collection with observations, interviews, and documentation. The analysis technique uses Miles and Huberman models. The conclusion is (1) strategies for planting religious values are habituation, teaching the values of goodness, nudity, repentance with istighatsah, and punishment; (2) The religious values instilled are personal and social worship; (3) the less successful factors of planting religious values are less aware learners, teachers have difficulty supervising students, parents are less exemplary, and socio-cultural environments are less supportive. Simultaneously, the success factor is compact managers, adequate facilities and infrastructure, strict school discipline application, passionate teachers, sincere, and professional managers applying the pesantren system.